Residents’ Attitudes Toward Place Marketing and Pro-environmental Behaviors at UNESCO World Heritage Sites - Ferreira, Sandra (2022)
In recent years, discussion on residents’ place attachment connection with world heritage sites (WHS) has started to increase in tourism research. Be-sides tourists' recognition and attraction of UNESCO World Heritage Sites, local people are important stakeholders that generate self-attachment to the place of living, thereby greater tendency to engage in pro-environmental behavior. In this vein, understanding place attachment is essential in planning for sustainable tour-ism development to conserve the physical environments as well as the meanings of places with cultural significance. However, a small number of studies have been discussing the important phenomenon of local residents’ place attachment in relation to pro-environmental attitudes and behaviors in cultural heritage tour-ism contexts. Therefore, this study discusses residents’ place attachment and pro-environmental behaviors toward specific UNESCO WHSs in Portugal. It devel-ops and proposes a conceptual framework that integrates residents’ place attach-ment to WHS, and their general and site-specific sustainable heritage behavior and presents their interrelationships in form of hypotheses. Final considerations and future researches paths are discussed.